Terpene Synthases in Rice Pan-Genome and Their Responses to Chilo suppressalis Larvae Infesting - Sun, Yang; Zhang, Pei-tao; Kou, Dou-rong; Han, Yang-chun; Fang, Ji-chao; Ni, Jiang-ping; Jiang, Bin; Wang, Xu; Zhang, Yong-jun; Wang, Wei; Kong, Xiang-dong (Frontiers in Plant Science, 2022)
Terpene synthase (TPS) catalyzes the synthesis of terpenes, and plays an important role in plant defence. This study identified 45 OsTPS genes (32 core genes and 13 variable genes) based on the high-quality rice gene-based pan-genome. This indicates limitations in OsTPS gene studies based on a single reference genome. In the present study, through collinearity between multiple rice genomes, one OsTPS gene absent in the reference (Nipponbare) genome was found and two TPS genes in the reference genome were found to have atypical structures, which would have been ignored in a single genome analysis. OsTPS genes were divided into five groups and TPS-b was lost according to the phylogenetic tree. OsTPSs in TPS-c and TPS-g were all core genes indicating these two groups were stable during domestication. In addition, through the analysis of transcriptome data, some structural variations were found to affect the expression of OsTPS genes. Through the Ka/Ks calculation of OsTPS genes, we found that different OsTPS genes were under different selection pressure during domestication; for example, OsTPS22 and OsTPS29 experienced stronger positive selection than the other OsTPS genes. After Chilo suppressalis larvae infesting, 25 differentially expressed OsTPS genes were identified, which involved in the diterpene phytoalexins precursors biosynthesis and ent-kaurene biosynthesis pathways. Overall, the present study conducted a comprehensive analysis of OsTPS genes using a high-quality rice pan-genome, which provided a basis for further study of OsTPS genes.